2023
DOI: 10.1002/ehf2.14426
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐utility analysis of add‐on dapagliflozin in heart failure with preserved or mildly reduced ejection fraction

Abstract: Aims The DELIVER study demonstrates a significant improvement in cardiovascular death or hospitalization for heart failure among heart failure with mildly reduced ejection fraction (HFmrEF) or heart failure with preserved ejection fraction (HFpEF).Cost‐utility of the adjunct use of dapagliflozin to standard therapy among patients with HFpEF or HFmrEF remains unclear. Methods and results A five‐state Markov mode was constructed to project health and clinical outcomes of the adjunct use of dapagliflozin to stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The incremental costeffectiveness ratios were £7,761, €9,540, and €5343/QALY in the United Kingdom, Germany, and Spain, respectively (Booth et al, 2023). Similarly, Tang and Sang. (2023) performed a cost-utility analysis based on the DELIVER study and the national statistical database.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The incremental costeffectiveness ratios were £7,761, €9,540, and €5343/QALY in the United Kingdom, Germany, and Spain, respectively (Booth et al, 2023). Similarly, Tang and Sang. (2023) performed a cost-utility analysis based on the DELIVER study and the national statistical database.…”
Section: Discussionmentioning
confidence: 88%
“…(2023) performed a cost-utility analysis based on the DELIVER study and the national statistical database. The study showed that the adjunct use of dapagliflozin to standard of care among patients with HFpEF or HFmrEF was cost-effective in China at a willingness-to-pay value of $12,652.5/QALY ( Tang and Sang, 2023 ). Most recently, Cohen et al (2023) performed an economic evaluation using a simulation model of US adults with HFpEF who meet the eligibility criteria of the EMPEROR-Preserved or DELIVER trials.…”
Section: Discussionmentioning
confidence: 99%
“…Another SGLT2 inhibitor, dapagliflozin, also showed a good cost‐effectiveness compared with SoC alone in patients with HFpEF in perspectives from a Chinese public healthcare 36 and public payers in European countries. 37 They assessed the cost‐effectiveness of dapagliflozin added to SoC compared with SoC alone based on the Dapagliflozin Evaluation to Improve the Lives of Patients with Preserved Ejection Fraction Heart Failure (DELIVER) trial, which was a placebo‐controlled trial in chronic HF patients with left ventricular ejection fraction > 40% that demonstrated a significant improvement in the combined incidence of HHF and CV death in patients treated with dapagliflozin added to SoC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies have demonstrated the cost-effectiveness of dapagliflozin in the whole spectrum of HF patients, regardless of the healthcare system of different countries [122][123][124][125][126][127][128]. In fact, the immediate initiation of dapagliflozin provides greater clinical benefits [128].…”
Section: Discussionmentioning
confidence: 99%